Photoconductivity & photoelectron emission of LiGaO2 crystal excited in intrinsic absorption range - Trukhin, Anatoly N.; Trinkler, Laima E. (Elsevier B.V., 2019)
The photoelectric response spectra were studied in a LiGaO2 crystal. The obtained spectra were interpreted as the release and diffusion of charge carriers, as well as external photoemission of electrons. The charge carrier release starts from excitation with a photon with energy greater than the optical gap of the LiGaO2 crystal (∼6 eV). The efficiency of generation of charge carriers exponentially increases up to 8 eV with saturation beginning from 9 eV. The nature of the photoelectric response is attributed to the Dember effect corresponding to the higher mobility of electrons compared to holes. The low yield of the internal photoelectron in the range of the intrinsic absorption band at 6 eV is associated with its exciton nature. Above 9.5–10 eV, an additional response was revealed that was interpreted as external photoelectron emission with a threshold of about Eth = 10.1 ± 0.2 eV. The relative emission yield of electrons increases as (hν - Eth)3, which corresponds to indirect transitions between the valence and conduction bands. The emission of photoelectrons for the direct band-to-band transitions increases linearly with the photon energy and the corresponding threshold is defined as 12.7 ± 0.2 eV.
This research is funded by the Latvian Council of Science, project “Research of luminescence mechanisms and dosimeter properties in prospective nitrides and oxides using TL and OSL methods], project No. lzp-2018/0361.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; LiGaO2 crystal; Electronic structure; Photoconductivity; Photoelectron emission; Photoluminescence; Vacuum ultraviolet